FAKTOR - FAKTOR YANG MEMPENGARUHI ARUS KAS MASA DEPAN (Studi Empiris Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2010-2013) - Seli Theresia Wantania, 12.05.52.0074; Nurhayati, Ida (Students Journal of Accounting and Banking, 2016)
The study examines the effect of earnings, cash flows, changes in receivables, changes in payables, changes in inventories and depreciation on future cash flows. This research was conducted at the Indonesian Stock Exchange by using a go public LQ 45 company as the unit of analysis. The sampling method used purposive sampling with the obsevation period from 2010 to 2013. Relationship and (or) influence between variable is described by using multiple regression. The result showed that the earnings and cash flows has positive effect and significant to the future cash flows. Whereas the changes in receivables, changes in payables, changes in inventories and depreciation had no significant effect on future cash flows.Keywords: Earnings, Cash Flows, Changes In Receivables, Changes In Payables, Changes In Inventories, Depreciation, Future Cash Flows